Identifikasi Taman Telajakan di Desa Penglipuran, Kecamatan Bangli, Kabupaten Bangli - Harianggara, Dewa Ngakan Made; Sugianthara, Anak Agung Gede; Krisnandika, Anak Agung Keswari (Jurnal Arsitektur Lansekap; Vol.9, No.2, Oktober 2023DO - 10.24843/JAL.2023.v09.i02.p09, 2023)
Identification of the Telajakan Park in Penglipuran Village, Bangli District, Bangli Regency. Penglipuran Village is one of the Tourism Villages in Bangli Regency which is unique in its spatial pattern and building architecture, including the telajakan garden. However, the arrangement of the telajakan garden in the Penglipuran Village area which is a tourist destination with an area that is not a tourist destination has a quite different arrangement. The purpose of this study was to identify the function, pattern of the telajakan garden and the enthusiasm of the community in managing and preserving the telajakan garden in Penglipuran Village. This research was conducted by survey method with data collection techniques in the form of interviews, questionnaires, field observations and literature study. Based on the research that has been done, the results show that the Telajakan garden in Penglipuran Village has a function as a support for tourist attractions, as a space or distance between the walls of the house and the highway, as a green open space, a place to stick a penjor, other supporting elements such as a place to stick a flag, strengthen the walls of the pengengker, as well as a place to socialize the community. The pattern of the telajakan garden in the area within the Penglipuran Village with the outskirts of the Penglipuran Village has differences, among others, in the angkul-angkul section and the position of the telajakan garden. The enthusiasm of the people of Penglipuran Village in preserving the telajakan garden is very high, the telajakan garden in Penglipuran Village is fully regulated in the awig-awig of Penglipuran Village. It is hoped that the community will continue to maintain the sustainability and beauty of the telajakan garden as a green open space and a cultural heritage of Balinese traditional gardens.